Review of Literature Management of Earnings in the Corporate Sector in Baddi, Himachal Pradesh (India): A Study of Selected Companies: A Review of Literature on Earnings Management in the Corporate Sector in Baddi, Himachal Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The aim of this paper is to examine the findings of the existing empirical studies on the above-mentioned issues of earning management decisions so as to find their answers. The research studies reviewed herein have been sourced from various national and international journals on the subject under reference and libraries of high repute in India, besides various web sites. On account of the subject ‘corporate finance’ being highly important, we find very comprehensive works on its various aspects in both advanced as well as emerging economies of the world Hence it was not possible to make review of each and every available study. So, we have resorted to a review of selected studies. Only those studies are covered which are most often quoted in the books, doctoral theses and research journals concerning financial economics.